Pendampingan pengajaran tentang gizi dan kesehatan di masa pandemi Covid-19 pada guru taman kanak-kanak - Herni Dwi Herawati; Herwinda Kusuma Rahayu; Ruwet Rusiyono (Unri Conference Series: Community Engagement, 2021)
The consumption of vegetables and fruit for the Indonesian population is currently still below the recommended one. The potential for low consumption of vegetables and vegetables is found in children, especially preschoolers. Preschoolers enter an important phase that will determine eating habits and behavior. For this reason, nutrition education is needed in order to increase children's love for healthy food. Efforts to foster a love of healthy food in children are needed by educators. The problems that arise faced by educators are the lack of knowledge related to child nutrition education and the right media and methods to introduce nutrition education in the era of the Covid 19 pandemic. Service activities have provided educators, knowledge related to nutrition education for preschool children, simulation of child health protocols in schools and making appropriate learning media for preschoolers during the Covid 19 pandemic by the Nutrition Science Study Program Service Team of the Faculty of Health Sciences in collaboration with the Elementary School Teacher Education Study Program Elementary School Teachers Faculty of Teacher Training and Education, Alma Ata University. The service method used goes through three stages, namely the preparation stage, the implementation stage and the evaluation stage. All these stages are directly accompanied by the service team. The location of this service activity is in TK Negeri 1 Pajangan, Pajangan, Bantul, Yogyakarta Special Region. The results of the activity evaluation show that the knowledge of nutrition education that has been given has increased from the average knowledge score between pre and post-test which has increased from 70 to 73.87. Educators have also been able to apply health protocols in schools, namely by practicing 4 M and being able to make learning media in the form of learning videos.